Evaluating multispecies landscape connectivity in a threatened tropical mammal community. Issue 1 (25th July 2014) - Brodie, Jedediah F.; Giordano, Anthony J.; Dickson, Brett; Hebblewhite, Mark; Bernard, Henry; Mohd‐Azlan, Jayasilan; Anderson, Jesse; Ambu, Laurentius
Abstract Habitat corridors are important tools for maintaining connectivity in increasingly fragmented landscapes, but generally they have been considered in single‐species approaches. Corridors intended to facilitate the movement of multiple species could increase persistence of entire communities, but at the likely cost of being less efficient for any given species than a corridor intended specifically for that species. There have been few tests of the trade‐offs between single‐ and multispecies corridor approaches. We assessed single‐species and multispecies habitat corridors for 5 threatened mammal species in tropical forests of Borneo. We generated maps of the cost of movement across the landscape for each species based on the species' local abundance as estimated through hierarchical modeling of camera‐trap data with biophysical and anthropogenic covariates. Elevation influenced local abundance of banded civets (Hemigalus derbyanus) and sun bears (Helarctos malayanus). Increased road density was associated with lower local abundance of Sunda clouded leopards (Neofelis diardi) and higher local abundance of sambar deer (Rusa unicolor). Pig‐tailed macaque (Macaca nemestrina) local abundance was lower in recently logged areas. An all‐species‐combined connectivity scenario with least‐cost paths and 1 km buffers generated total movement costs that were 27% and 23% higher for banded civets and clouded leopards, respectively, than the connectivity scenarios for those species individually. A carnivore multispecies connectivity scenario, however, increased movement cost by 2% for banded civets and clouded leopards. Likewise, an herbivore multispecies scenario provided more effective connectivity than the all‐species‐combined scenario for sambar and macaques. We suggest that multispecies habitat connectivity plans be tailored to groups of ecologically similar, disturbance‐sensitive species to maximize their effectiveness. Evaluación de la Conectividad de Terrenos Multiespecie en una Comunidad Tropical de Mamíferos